A feasibility study on real-time evaluation of concrete surface crack repairing using embedded piezoceramic transducers. (July 2018) - Feng, Qian; Cui, Jun; Wang, Qiuliang; Fan, Shuli; Kong, Qingzhao
Abstract: Surface cracking in large-scale concrete structures are inevitable, and some cracks shall be repaired to prevent further structural damages. Various methods of repairing surface cracks in concrete structures have been studied, however, evaluation of repairing of those cracks, especially through real time means, have not much been reported. In this paper, a feasibility study was performed on evaluation of repairing concrete surface crack in real-time using embedded piezoceramic-based transducers, called Smart Aggregates (SA). Using the active sensing approach, a pair of SAs in a concrete structure can communicate through generating and detecting stress wave. In the experimental study, three concrete beam specimens were investigated. In each specimen, four smart aggregates were embedded in the beam with two designed surface cracks. Subsequently, these two cracks were repaired by using mortar and Carbon Fiber Reinforced Polymer (CFRP) sheet. Due to interfacial properties among the three different interfacial conditions: the healthy concrete structure, the concrete structure with a crack, and the concrete structure with a repaired crack, the stress wave attenuation characteristics differ. The received signals of SAs among those three interfacial conditions were compared in time domain. In addition, a wavelet packet-based energy analysis was performed to quantitatively indicate the energy value of the received signal. Experimental results shows that the signal energy values computed by the wavelet packet-based energy analysis has potential to determine the crack occurrence in concrete structures and to help evaluate the repair effects.